"A Thing Apart": Controlling Male Family Migration to the United Kingdom. (October 2015) - Wray, Helena
Although gender offers valuable perspectives for understanding migration law, masculinity has received little attention. In family migration, men are generally regarded as economic agents and family as marginal to their lives, a view that is difficult to dislodge because it serves the purposes of governments anxious to reduce unwanted immigration. In British immigration law, measures have often explicitly or implicitly relied on such gender-based assumptions. Recently, lawyers have utilized the gap between official and unofficial standards by promoting test cases involving either a woman or a vulnerable man but where the principles established will benefit all migrants. Gains may be short-lived however as new ways emerge of making distinctions. These arguments are demonstrated in this article through examination of British immigration control and judicial decisions. The article finds that, in this arena, new understandings of masculinity and fatherhood have yet to make much impact.